2020
DOI: 10.1186/s12284-020-00409-0
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Effects of Soluble Starch Synthase IV-2 and It with ADPglucose Pyrophorylase Large Unit and Pullulanase on Rice Qualities

Abstract: Background Rice amylose content and amylopectin structure corporately determine rice eating and cooking qualities (ECQs). Soluble starch synthase ( SS ) IV-2 is a member of the soluble starch synthesis gene family but with unknown effects on ECQs. Results In this study, three populations derived from a cross of two parents who possess the same major genes of starch bio-synthesis were employ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…As in earlier studies, we found that SBE1, BEIIb, SSIVb, and PUL affected GC (He et al, 2006;Tian et al, 2009;Xu et al, 2020). Besides, ISA1, SSIIc, BEIIa, and SSIIa were also associated with GC, and their genetic effects decreased in order (Table 4).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…As in earlier studies, we found that SBE1, BEIIb, SSIVb, and PUL affected GC (He et al, 2006;Tian et al, 2009;Xu et al, 2020). Besides, ISA1, SSIIc, BEIIa, and SSIIa were also associated with GC, and their genetic effects decreased in order (Table 4).…”
Section: Discussionsupporting
confidence: 84%
“…Furthermore, the effects of SSIVb and its interaction with AGPlar and pullulanase (PUL) are vital for rice quality breeding under the background of the same major genes (Xu et al, 2020). Many studies favored understanding the genetic basis of rice qualities by quantitative trait loci (QTLs) mapping (Leng et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…It is noteworthy that mutation of SSIV-2 or SSIIIa had no significant effect on rice starch granule morphology, but their combination resulted in small and spherical starch granules ( Toyosawa et al., 2016 ). Recently, it has been confirmed that the interaction of AGPlar and PUL contributes to rice ECQ ( Xu et al., 2020 ). The mutation of individual SS genes usually leads to undesirable grain quality traits (i.e., SSIII-1 ) and minor changes in ECQ ( Huang et al., 2021a ; Zhu et al., 2021 ).…”
Section: Genetic Basis Of Rice Ecq Improvementmentioning
confidence: 93%
“…Therefore, it was concluded that the effects of SSIIa, GBSSI, and ISA1 gave greater influence than the other genes derived from parental japonica and indica lines. The minor differences observed between these two lines may be due to nucleotide polymorphisms found in other genes, such as SSIVb and AGPase, and that may give minor effects on the properties of starch (Xu et al 2020). To eliminate the minor effects of other genes, it is necessary to perform backcrossing to produce near isogenic lines or to perform targeted insertion of transgenes.…”
Section: Traits Of New Rice Linesmentioning
confidence: 99%